Bioclimatic Resources and Their Consideration for Tourism Development in Selected Destinations of Uzbekistan - Bakhtiyar Makhamatjanovich Kholmatjanov; Yuriy Vasilevich Petrov; Farrukh Ilkhomjon ugli Abdikulov Abdikulov; Mokhichekhra Rustam kizi Abdikulova; Zafariddin Fakhriddin ugli Saypiddinov; Mukhammadismoil Mukhitdinovich Makhmudov; Farkhod Makhamatjanovich Khalmatjanov; Firuz Bakhrametdinovich Safarov (Universitas Muhammadiyah Sidoarjo, 2020)
Taking into account bioclimatic conditions of a territory is one of the necessary elements for the tourism industry. In order to assess the bioclimatic conditions of selected settlements of Uzbekistan, such as Samarkand, Dagbit, Tashkent and the Chimgan mountain recreation zone, a thermohygrometric coefficient of air aridity is used. It is shown that the coefficient has a good response to changes in temperature and humidity and a clearly defined tendency in its annual and daily course. Based on the statistical processing of the data series of standard observations of air temperature and dew point at Samarkand, Dagbit, Tashkent Observatory and Chimgan meteorological stations for the period of 2009-2018 the spatial-temporal features of distribution of thermal comfort conditions are revealed.